2005
DOI: 10.1007/s00405-005-0951-0
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal facial nerve course associated with stapes fixation or oval window absence: report of two cases

Abstract: Congenital minor ear malformations are very uncommon. Their etiology can be explained by the embryological development of the middle ear structures. Their classification, diagnosis and treatment pose certain problems. We report on one case of congenital stapes fixation and one case of oval window absence, both associated with an abnormal facial nerve course. Good long-term results show that performing a platinotomy or vestibulotomy in cases of congenital stapes fixation or oval window absence can be a relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…Thus, six single‐case reports were included in this report along with larger sample reports . In addition to single‐case reports, there were also eight studies with the total number of cases less than 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, six single‐case reports were included in this report along with larger sample reports . In addition to single‐case reports, there were also eight studies with the total number of cases less than 10 …”
Section: Discussionmentioning
confidence: 99%
“…1,[16][17][18][19][20] In addition to single-case reports, there were also eight studies with the total number of cases less than 10. 3,7,[21][22][23][24][25][26] Looking at the meta-analysis graph, we can see that small squares for each study are shown in different sizes depending on the sample size. Studies that reported more successful surgical results appear in the graph to be leaning to the right, whereas unsuccessful ones appear to be leaning to the left.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, current literature is now focusing on the potential role of cone beam CT, which has demonstrated similar efficacies with a lower radiation dose as compared with HRCT [ 21 ]. Malposition of the facial nerve is often associated with oval window atresia [ 20 , 22 ]. It has been suggested that this may prevent contact between the stapes and otic capsule, thus inhibiting normal development of both structures [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand it was also reported that inner ear fenestration surgery results in improvement in hearing with stable results [12]. In addition, vestibulotomy in cases of oval window absence is a relatively safe and effective procedure, which can be performed even in the presence of abnormal facial nerve passing under the oval window or its area in cases of oval window dysplasia [17]. Despite the difference in results, stapedectomy for congenital fixation remains an effective method to achieve significant hearing improvement in the majority of patients [18].…”
Section: Discussionmentioning
confidence: 99%